ETHNOBOTANY SAGO (Metroxylon sago Rottb) in JAILOLO LOCAL COMMUNITY, WEST HALMAHERA REGENCY, INDONESIA - Hasan, Said; Tolangara, Abdulrasyid; Ahmad, Hasna; Sahil, Jailan; Suparman, Suparman (Universitas Tanjungpura, 2024)
Sago plants have long played an important role in people's lives, particularly in eastern Indonesia